ACUTE ORAL TOXICITY STUDY OF ETHANOLIC EXTRACT OF ACTINOSCIRPUS GROSSUS (L.F.) GOETGH. AND D.A. SIMPSON - Ganapathi, Savin Chanthala; Holla, Rajendra; Ym, Shivaraja Shankara; Mundugaru, Ravi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: To study the acute oral toxicity of ethanolic extract of Actinoscirpus grossus (L.f.) Goetgh. and D.A. Simpson in Wistar albino rats. Methods: Ethanolic extract of the plant was assessed for single dose acute toxicity by employing Organisation for Economic Co-Operation and Development(OECD) guidelines 425 using Acute Oral Toxicity(AOT) software. The dosed (up or down as per the requirement) rats were observed for 14 days for general appearance, behavior, mortality, and necropsy. A total of 5 healthy female rats of body weight 225Â±25 g were used. Results: The test substance did not produce any mortality up to the dose of 2000 mg/kg per oral. Conclusion: Test substance is without any toxic potential even at the dose of 2000 mg/kg in animals and the Lethal Dose (LD50) value of A. grossus (L.f.) Goetgh. and D.A. Simpson was found to be more than 2000 mg/kg body weight.